αV-class integrins exert dual roles on α5β1 integrins to strengthen adhesion to fibronectin - Mitasha Bharadwaj (Nature Portfolio, 2017)
Interaction of fibronectin with αv-class and α5β1 integrins results in formation of cell adhesion complexes, but the initial events (<120 s) remain unclear. Here, the authors show that αv-class integrins bind fibronectin faster than α5β1 integrins and subsequently signal to α5ß1 integrins to strengthen the adhesion.